IMPLEMENTASI METODE BERMAIN PERAN DALAM MENGEMBANGKAN KEMAMPUAN SOSIAL ANAK USIA DINI DI PAUD PLAMBOYAN 3 KARAWANG - Dwiputri, Intan Aulia; Muis, Abdul; Dewi, Ratna Sari (IKIP Siliwangi, 2025)
This study emphasizes the importance of early childhood education (PAUD) as a golden period in shaping children's character and social skills. The main objective of this study is to describe the application of role-playing methods in improving the quality of children's social interactions. A qualitative approach was used with a case study method, involving five informants consisting of a school principal, two educators, and two parents of students. Data were collected through participatory observation, focused interviews, and documentation in the form of photos of activities, anecdotal notes, and child development observation sheets. Data analysis was carried out through reduction, presentation, and conclusion drawing with validity testing using triangulation of sources, techniques, and time. The results showed that role-playing encouraged children to recognize various social roles in life, develop the ability to express emotions, express opinions, and appreciate differences. Educators acted as facilitators who designed contextual learning scenarios based on everyday life themes. A conducive learning environment and the availability of learning media also support the success of this method. The evaluation was conducted through anecdotal notes and children's social observation sheets. The research concluded that role-playing effectively fosters empathy, communication, and emotional control. Further training for teachers is recommended to ensure more structured and optimal implementation.